Successful Approach Implementasi Talent Mapping: Studi pada PFA di BPKP - Nova Betries Situmorang; M. Husni Thamrin; Abdul Nadjib (Research and Development Agency Ministry of Home Affairs, 2021)
Most research on talent management concentrates on the theory and practice of talent mapping in the private sector both domestic and foreign. Little research consider talent mapping in the public sector. Thus this research investigates how the implementation of talent mapping in public sector due to the stipulation of civil servant management in the recent years and many institutions have not applied it yet. Talent mapping is a crucial initial stage and determines the success of the human resource development process in talent management. The aim of this research is to know what factors have a significant affect to the successful implementation of the talent mapping in BPKP. This research is a quantitative research by distributing questionnaires to 72 Employees of Human Resource Department of BPKP. The variables are used to analyze the factors that affecting such as standard and objectives, resources, communication and enforcement activities, the characteristics of the implementing agencies, social, economic, and political conditions and the disposition of implementors. The result based on perceptions of implementors using data analysis of Structure Equation Modeling-Partial Least Square (PLS SEM) shows that the successful implementation of talent mapping policy for auditors is affected significantly and positively by communication and enforcement activities, the characteristics of the implementing agencies, and social, economic, and political conditions. So, to achieve the succeeding level in the best result, it can be done by some solution such as maintaining accuracy and consistency of communication and enforcement activities, improving the characteristics of implementing agencies, and maximizing social, economic, and political conditions.